2020
DOI: 10.1111/jan.14582
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nurses' health policy participation: WSPPIR instrument development and psychometric evaluation

Abstract: Aim To measure nurses' health policy participation by developing and psychometrically testing the Waddell Spectrum for Policy Participation Influence and Research (WSPPIR) Instrument. Design Instrument development; based on a nursing conceptual framework. Methods This four‐phase study was conducted in 2018 to estimate content validity, construct validity, and internal consistency reliability of the WSPPIR instrument. Phase 1– item generation for the multi‐dimensional concept of health policy participation as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, Gazarian and colleagues (2022) found that the CMNHP has been used to guide 21 nursing dissertations but at only one institution, which happens to be the University of Massachusetts Boston, where I am a faculty member. Examples of these dissertations are by Connor (2017, 2018) and Waddell (2019, 2021). Connor (2017) studied the extent of nurses’ values for, knowledge about, and implementation of evidence-based practice and extent of implementation of the clinical practice guidelines for surgical site infections and central line–associated bloodstream infections.…”
Section: Explicit Nursing Conceptual Models For Health Policy Nursing...mentioning
confidence: 99%
“…In addition, Gazarian and colleagues (2022) found that the CMNHP has been used to guide 21 nursing dissertations but at only one institution, which happens to be the University of Massachusetts Boston, where I am a faculty member. Examples of these dissertations are by Connor (2017, 2018) and Waddell (2019, 2021). Connor (2017) studied the extent of nurses’ values for, knowledge about, and implementation of evidence-based practice and extent of implementation of the clinical practice guidelines for surgical site infections and central line–associated bloodstream infections.…”
Section: Explicit Nursing Conceptual Models For Health Policy Nursing...mentioning
confidence: 99%